2020
DOI: 10.1007/s10479-020-03664-y
|View full text |Cite
|
Sign up to set email alerts
|

Green food supply chain design considering risk and post-harvest losses: a case study

Abstract: The global food insecurity, malnourishment and rising world hunger are the major hindrances in accomplishing the zero hunger sustainable development goal by 2030. Due to the continuous increment of wheat production in the past few decades, India received the second rank in the global wheat production after China. However, storage capacity has not been expanded with similar extent. The administrative bodies in India are constructing several capacitated silos in major geographically widespread producing and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 77 publications
2
30
0
Order By: Relevance
“…We have followed the solution approach of Tiwari et al (2017), who state that analytical methods fail to solve a highly complex problem and require high computational work and analytics. Particle swarm optimization algorithm (PSO) has been used broadly to obtain feasible solutions based on the food-searching activities of birds (Mogale et al, 2020;Tiwari et al, 2017). We have adopted the PSO technique with a continuous iteration process due to its broader acceptance and applicability in perishable inventory management literature.…”
Section: Solution Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…We have followed the solution approach of Tiwari et al (2017), who state that analytical methods fail to solve a highly complex problem and require high computational work and analytics. Particle swarm optimization algorithm (PSO) has been used broadly to obtain feasible solutions based on the food-searching activities of birds (Mogale et al, 2020;Tiwari et al, 2017). We have adopted the PSO technique with a continuous iteration process due to its broader acceptance and applicability in perishable inventory management literature.…”
Section: Solution Methodologymentioning
confidence: 99%
“…Advances in research on IoT have evolved significantly since 2011, successfully fulfilling Industry 4.0 (Kamble et al, 2020b). The growth of MSMEs is central to warehousing, given the nature of business (Mogale et al, 2020). Hansen and Bøgh (2021) confirmed that MSMEs struggle to adopt advanced technologies due to a lack of resources, knowledge, dedicated strategies, and practical research implications.…”
Section: To Onwardsmentioning
confidence: 99%
“…There are other practical settings as addressed by Gupta et al [19] and Mogale et al [37], where the DEA approach can be applied in the revised contextual settings. It is also important to note that in case the problems become too complex such as in Mogale et al [36], then the dynamic DEA will be more appropriate to apply.…”
Section: Dea Approachmentioning
confidence: 99%
“…The profit-sharing contract adopted between the two parties (manufacturer and retailer) improved the communications between them, optimized the decisions, and increased the profit. Dnyaneshwar et al [18] developed a mathematical model with multiperiods and a single objective function to help the administrative bodies in India to decide about constructing several capacitated silos for storing wheat. The objective function of the proposed model was to minimize the overall food grain supply chain cost.…”
Section: Clsc Designmentioning
confidence: 99%